Teachers’ Beliefs, Knowledge and Practice of Learner-Centered Approach in Schools of Ethiopia - Yalew, Endawoke (The Ethiopian Journal of Education, 2023)
The purpose of this study was to examine the beliefs teachers hold and the knowledge they have about learner-centered approach as well as the degree to which they practice it in classroom settings. It also aimed at investigating the effects of beliefs, knowledge, empowerment, class size, teaching load, and year of service on teach ers’ practice of learner-centered approach. The data were collected from 635 in-service teacher training program participants at Bahir Dar University, Education Faculty, who were teaching different subjects at middle and high schools in almost all parts of the country. The results revealed that the teachers tend to employ mostly the traditional teacher-centered approach of teaching. Regression analysis indicated that the three most prominent factors that contributed significantly to the variance in practice were learner-centered belief about learning , learner and teaching (Factor 1), knowledge, and instructional empowerment. In other words, teachers who had knowledge of this teaching approach, those who were empow€ied to have the freedom to choose their own instructional approaches, and those who had learner-centered beliefs tended to apply student-centered approach in their classrooms. This may have implication to teacher education institutes in that there is a need to incorporate learner-centered approach in their programs in the training of would-be-teachers.